2004
DOI: 10.1002/ab.20045
|View full text |Cite
|
Sign up to set email alerts
|

Sex and age differences in victimisation and conflict resolution among adolescents in a south Australian school

Abstract: This study investigated the victimisation experiences and conflict resolution strategies of 591 adolescents (304 boys and 287 girls) enrolled in grades 8 (mean age 13.3 years), 9 (mean age 14.3 years), and 10 (mean age 15.4 years) in a metropolitan secondary school in Adelaide, South Australia. A modified self-report version of the Direct and Indirect Aggression Scales (DIAS) [Bjorkqvist et al., 1992b] and a conflict resolution questionnaire drawn particularly from the work of Feldman and Gowen [1998] were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
2
15

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 37 publications
10
64
2
15
Order By: Relevance
“…Sex differences were also established in the frequency with which conflict resolution styles are used, with girls being relatively higher in positive problem solving, withdrawal and compliance. These findings are in agreement with predictions, and results from previous studies [Feldman and Gowen, 1998;Hartup, 1992;Lindeman et al, 1997;Owens et al, 2005], showing that girls are more likely to behave constructively in conflict situations than boys.…”
Section: Discussionsupporting
confidence: 93%
“…Sex differences were also established in the frequency with which conflict resolution styles are used, with girls being relatively higher in positive problem solving, withdrawal and compliance. These findings are in agreement with predictions, and results from previous studies [Feldman and Gowen, 1998;Hartup, 1992;Lindeman et al, 1997;Owens et al, 2005], showing that girls are more likely to behave constructively in conflict situations than boys.…”
Section: Discussionsupporting
confidence: 93%
“…Factor analysis has confirmed the construct validity of the three subscales (Lagerspetz, Bjorkqvist, & Peltonen, 1988;Toldos, 2005). High levels of internal consistency have been found, ranging from 0.80 to 0.96, in subsamples that have used this instrument in a variety of cultural settings Owens, Daly & Slee, 2005;Salmivalli & Kaukiainen, 2004;Toldos, 2005).…”
Section: Methods Instrumentationmentioning
confidence: 67%
“…For gender, there are different results in literature. Some studies (Duncan, 1999;Moroschan, Hurd & Nicoladis, 2009) have indicated that males display higher aggression behavior, while others (Owens, Daly & Slee, 2005) have shown that females display higher aggression. However, other studies (Leeanare & Rinaldi, 2010;Osterman et al, 1994) have shown that there is no difference between the genders in aggression behaviors.…”
Section: Discussionmentioning
confidence: 99%